Effects of continuous supplementation of Acanthopanax senticosus Harms on the cardiac autonomic function of community-dwelling elderly individuals during resting and standing tests: a randomized controlled trial - Sato, Takeru; Aoki, Takumi; Ito, Yuki; Oishi, Kan; Fujishima, Masaki; Okumura, Eri; Ishii, Kojiro (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiac autonomic function (CAF) decreases with aging, and Acanthopanax senticosus Harms (ASH) consumption reportedly induces anti-stress effects. This study aimed to assess the effect of continuous supplementation of ASH on CAF during resting and standing tests in the elderly population.Methods: This double-blind, randomized controlled trial was conducted in the morning in a laboratory setting and was carried out between June 2017 and July 2017 at Kambaikan, Doshisha University (Karasuma-higashi-iru, Imadegawa-dori, Kamigyo-ku, Kyoto 602-8580, Japan). In total, 28 community-dwelling elderly individuals (mean ± standard deviation = 72.5 ± 4.5 years) were included. Each subject was instructed to consume ASH or placebo supplements twice daily for 4 weeks. An autonomic reflex orthostatic tolerance recorder was used to measure CAF in pre-and post-intervention phases. Parameters were measured in a seated position and included coefficient of variation of R-R intervals (CVRR), low frequency (LF), high frequency (HF), LF/HF ratio, blood pressure, and heart rate (HR). Changes in each parameter were evaluated before and after standing. All parameters were defined as the difference between the mean value obtained in a standing position for 2 minutes and that obtained in a 2-minute seated position. Results: A two-way analysis of variance revealed a significant group-time interaction effect on CVRR, HF, and ΔLF/HF ratio. Following the intervention, CVRR, HF, LF/HF ratio, systolic blood pressure (SBP), HR, ΔLF/HF ratio, ΔSBP, and ΔHR improved significantly in the ASH group only.Conclusions: Four-week supplementation of ASH improved CAF in community-dwelling elderly individuals during resting and standing tests.Trial Registration: The trial has been registered in the UMIN Clinical Trials Registry (UMIN000027251) on May 20, 2017.